Chronic hepatitis B virus infection and total and cause-specific mortality: a prospective cohort study of 0.5 million people. Issue 4 (9th April 2019) - Si, Jiahui; Yu, Canqing; Guo, Yu; Bian, Zheng; Meng, Ruogu; Yang, Ling; Chen, Yiping; Jin, Jianrong; Liu, Jingchao; Guo, Ziyan; Chen, Junshi; Chen, Zhengming; et al.
Abstract : Objectives: Chronic hepatitis B virus (HBV) infection is associated with a higher risk of liver diseases. Substantial uncertainty remains, however, about the associations of HBV infection with mortality from extrahepatic causes, especially from subtypes of cardiovascular diseases. We prospectively examined the association of chronic HBV infection with total and cause-specific mortality. Design: Population-based prospective cohort study. Setting: China Kadoorie Biobank in which participants from 10 geographically diverse areas across China were enrolled between 2004 and 2008. Participants: 475 801 participants 30–79 years of age without reporting major chronic diseases at baseline were enrolled. Hepatitis B surface antigen (HBsAg) was tested using an on-site rapid test strip at baseline. Primary and secondary outcome measures: Total and cause-specific mortality. Results: A total of 35 822 deaths were recorded during ~10 years of follow-up. In multivariable-adjusted analyses, compared with HBsAg-negative participants, HBsAg-positive participants had an increased risk of total mortality (HR=2.01, 95% CI: 1.91 to 2.12), which was higher in men (HR=2.16, 95% CI: 2.01 to 2.31) than in women (HR=1.74, 95% CI: 1.60 to 1.90). Presence of HBsAg was associated with increased mortality from liver cancer (1339 deaths, HR=13.95, 95% CI: 12.46 to 15.62), infections (410 deaths, HR=10.30, 95% CI: 8.21 to 12.94), digestive diseases (688 deaths, HR=6.83, 95% CI: 5.49 to 8.50), intracerebral haemorrhage (4077 deaths, HR=1.38, 95% CI: 1.14 to 1.68) and ischaemic heart diseases (4624 deaths, HR=1.31, 95% CI: 1.09 to 1.58). The positive association between HBsAg status and risk of death was stronger in participants younger than 50 years, smokers, physically active or non-hypertensive participants. Conclusions: Among Chinese adults, chronic HBV infection was associated with increased mortality from a range of hepatic and extrahepatic diseases.